2016
DOI: 10.1016/j.gerinurse.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of the Dementia Symptom Management at Home (DSM-H) program: An interprofessional home health care intervention to improve the quality of life for persons with dementia and their caregivers

Abstract: Home health care agencies are increasingly taking care of sicker, older patients with greater comorbidities. However, they are unequipped to appropriately manage these older adults, particular persons living with dementia (PLWD). We therefore developed the Dementia Symptom Management at Home (DSM-H) Program, a bundled interprofessional intervention, to improve the care confidence of providers, and quality of care delivered to PLWD and their caregivers. We implemented the DSM-H with 83 registered nurses, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 37 publications
0
43
0
1
Order By: Relevance
“…Despite the limited number of education and training programs that were specifically focused on informal caregivers (e.g., family caregivers), the majority of these studies found that programs were successful at improving self‐perceived competence and ability in providing care . Additionally, studies that focused on formal caregivers (e.g., nurse, physicians) found that education and training programs were successful at improving attitudes, communication, confidence and ability to provide care . However, there appears to be an underutilization of validated measures to assess knowledge programs for formal and informal dementia caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited number of education and training programs that were specifically focused on informal caregivers (e.g., family caregivers), the majority of these studies found that programs were successful at improving self‐perceived competence and ability in providing care . Additionally, studies that focused on formal caregivers (e.g., nurse, physicians) found that education and training programs were successful at improving attitudes, communication, confidence and ability to provide care . However, there appears to be an underutilization of validated measures to assess knowledge programs for formal and informal dementia caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…The most common population descriptor was community dwelling or older adults of a certain age 17 19 27 29 31 44 45. Underlying conditions included mild cognitive impairment and dementia (n=5),18 28 30 32 34 cardiac conditions (n=4),15 24–26 stroke (n=3),22 38 40 falls and fear of falling (n=3),21 35 48 hip fracture (n=2),37 39 diabetes (n=2),14 41 42 breast cancer,20 Parkinson’s disease,16 depression,23 chronic health problems,33 osteoarthritis,36 leg ulcer,43 neck pain46 and foot problems 47…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were from the UK (n=17),14 15 17 19 20 22 31 34–42 47 Netherlands (n=6),26 27 30 44 45 48 USA (n=4),18 24 25 28 Canada,16 India,23 Germany,29 46 Hong Kong,32 Italy,33 and Belgium 43. Ten studies were linked to other publications reporting the same intervention or other aspects of the development process 22 25 26 28 29 31 35 39 42 43…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using 2016 adjusted costs, the average annual per-person payment for postacute care for Medicare beneficiaries with Alzheimer's and other dementias was 11.5-times greater than older adults without dementia; this is a high risk group [17]. Other research findings emphasize the role of appropriate postacute care in influencing patient and caregiver satisfaction and improving the quality of patients' lives [18,19]. However, relatively little is known about how to affect patterns of postacute care service use among high-risk cognitively impaired patient groups and what impacts programs targeted to this group will have on total costs of posthospitalization care.…”
mentioning
confidence: 99%